2016
DOI: 10.18203/2320-6012.ijrms20164531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aloe vera gel application on epidermal wound healing in the domestic rabbit

Abstract: Background: A wound is a breakdown in the protective function of the skin or loss of continuity of epithelium, with or without loss of underlying connective tissues, muscles, nerves, bones following injury to the skin, surgery, a blow, cut, chemicals, heat, cold, friction, shear force, pressure or diseases such as leg ulcers or carcinomas. A study was undertaken to determine the healing properties of Aloe vera gel on epidermal wounds in rabbits.Methods: Twelve adult rabbits were divided into two groups randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Several other studies have also reported on biochemical studies that Aloe vera has revealed significant increase in collagen and decreased hexosamine content and malondialdehyde levels when compared with control (Yadav et al, 2012). The same thing is also shown by (Kayode, 2016) who has tested the effect of Aloe vera gel application on epidermal wound healing in the domestic rabbit. The results showed that animals treated with Aloe vera gel had significantly (p<0.05) faster rates of healing with shorter days of scab fall off than the control and showed significant (P<0.05) changes in the packed cell volume, mean corpuscular volume, lymphocyte and neutrophil counts (Kayode, 2016).…”
Section: Results and Discussion Evaluation Results Of Aloe Vera Extrasupporting
confidence: 60%
“…Several other studies have also reported on biochemical studies that Aloe vera has revealed significant increase in collagen and decreased hexosamine content and malondialdehyde levels when compared with control (Yadav et al, 2012). The same thing is also shown by (Kayode, 2016) who has tested the effect of Aloe vera gel application on epidermal wound healing in the domestic rabbit. The results showed that animals treated with Aloe vera gel had significantly (p<0.05) faster rates of healing with shorter days of scab fall off than the control and showed significant (P<0.05) changes in the packed cell volume, mean corpuscular volume, lymphocyte and neutrophil counts (Kayode, 2016).…”
Section: Results and Discussion Evaluation Results Of Aloe Vera Extrasupporting
confidence: 60%
“…The erythropoietin effects of A. vera extracts in hemotopoietic cells of bone marrow have been reported (Iji et al 2010). The assumption is that these effects could be due to vitamins such as beta carotene, C, E, B 12 , riboflavin, thiamine, and folic acid, minerals (calcium, chromium, copper, selenium, manganese, potassium, sodium, and zinc essential and nonessential amino acids) present in A. vera that are essential for the synthesis of hemoglobin as demonstrated in Kayode (2016). Erythropoiesis has also been attributed to polysaccharides present in A. vera leaves (Ni et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…An aloe vera extract given to the rabbit wounds had significantly affected the wound contraction, especially in the proliferative and maturation phases. 17 There are also no studies that directly examine the effect of aloe vera extract in increasing the FGF expression levels on the wound healing process of hyperglycemic. Therefore, the present study is the first study that examined and compared the effects of Lagerstroemia speciosa and aloe vera on hyperglycemia-induced rats' wound healing process by observing the FGF-2 expression level.…”
Section: Discussionmentioning
confidence: 99%